Community radio in Indonesia. A re-invention of democratic communication. - Hollander, Ed; Hidayat, Dedy Nur; d’Haenens, Leen (Javnost-The Public, 2008)
This paper discusses the ways in which eff orts aimed at democratising the media system and empowering communities in Indonesia in three discursive periods (the 1998 “Revolution Movement,” the “Reform Era” follow-up, and the 2002 Broadcasting Act up till the present time) have ebbed and flowed. The main result of the changing winds so far has been the liberalisation of the market, in line with global media trends. The Government has tried to frustrate the prospects of community media. Hence, the current development of community radio in the country remains stagnant, the main challenge being to create a more visible position in the media landscape, which in turn may bring about a more supportive stance in the government’s policies. Our tour d’horizon of the state of affairs of community radio, its complementary status to the mainstream national media scene, and the assessment of current needs are based upon empirical evidence gathered in the Manado and Jogyakarta areas. Departing from the different dynamics of these two cases, weaknesses and critical success factors will be assessed, taking into account the different backgrounds of the regions, radio practitioners as well as their audiences in terms of religion, ethnicity, and life styles.